Ethics and Managers: (Mis)Alignment of Managers’ Values With the Perceived Values in Their Decision-Making Strategies - Mladenović, Milena; Novak, Vesna (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
In this paper, we first define the basic concepts and then delve into the values of managers and their their relevance for ethical decision-making. Next, we introduce a model of ethical decision-making that greatly influenced our research model. The aim of our model was to assess the alignment between managers' value systems and those recognized in their decision-making strategies. Through a survey of managers and their employees, we uncovered significant discrepancies between the values represented by managers and those embedded in their decision-making strategies. Notably, gender plays a role, with female managers showing partial discrepancy and male managers exhibiting absolute discrepancy. Additionally, we observed differences in the level of ethical conduct between male and female managers, with female managers displaying higher level of ethical conduct. These findings provide valuable insights for further research and discussions in academic and broader contexts.